A hesitant fuzzy extension of VIKOR method for evaluation and selection problems under uncertainty. (2017) - Foroozesh, N.; Gitinavard, H.; Mousavi, S. Meysam; Vahdani, Behnam
In complex real-world problems, hesitant fuzzy sets could help experts or decision makers (DMs) when they are hesitant among several performance values and can express their judgments as a set of possible values for an element between zero and one. In this respect, the main purpose of this paper is to present hesitant fuzzy information to develop the vlsekriterijumska optimizacija i kompromisno resenje in serbian (VIKOR) method, namely HF-VIKOR by utilising the weights of decision makers and distance measure along with proposing a new index for the ranking process of compromise solution procedure. The hesitant fuzzy hamming distance measure is applied to compute the utility measure and regret measure; also, hesitant fuzzy Euclidean distance measure is used to compute the proposed new index for the evaluation of alternatives by considering risk preferences of DMs. Moreover, two application examples about new product selection and energy policy selection problems under uncertainty are presented to indicate the suitability of the proposed HF-VIKOR method, and then it is compared with the recent methods from the literature. Finally, sensitivity analysis is considered to indicate effects of the DMs' weights on preference order ranking.